2017
DOI: 10.1002/jgm.2997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors are stressed variably by onset age‐based sample selection in psoriasis: A hint from major histocompatibility complex region‐based analysis

Abstract: Onset age-based sample variables influence the results of genetic association studies, at least in MHC region-based genetic analysis. We suggest that caution is required when selecting samples for genetic association studies to prevent confounders that might be a result of onset age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…We constructed a Han-MHC database and identified eight independent susceptibility loci associated with psoriasis, including HLA-C * 06:02, amino acids at positions 9 and 67 in HLA-B, HLA-C * 07:04, rs118179173, amino acid at position 116 in HLA-B, DPB1 * 05:01, and amino acid at position 281 in BTNL2 9 . Moreover, by analyzing genetic associations between psoriasis subphenotypes divided by age of onset and shared control subjects, our group found that the number of susceptible variants decreased as the onset age of psoriasis increased 10 . In addition, several other genetic studies have reported that HLA-C * 06 is more strongly associated with EOP in various races 11 .…”
Section: Introductionmentioning
confidence: 99%
“…We constructed a Han-MHC database and identified eight independent susceptibility loci associated with psoriasis, including HLA-C * 06:02, amino acids at positions 9 and 67 in HLA-B, HLA-C * 07:04, rs118179173, amino acid at position 116 in HLA-B, DPB1 * 05:01, and amino acid at position 281 in BTNL2 9 . Moreover, by analyzing genetic associations between psoriasis subphenotypes divided by age of onset and shared control subjects, our group found that the number of susceptible variants decreased as the onset age of psoriasis increased 10 . In addition, several other genetic studies have reported that HLA-C * 06 is more strongly associated with EOP in various races 11 .…”
Section: Introductionmentioning
confidence: 99%